Hadith #1529 - Sunan al-Nasa'i - al-Aswad bin Hilal al-Maharbi الأسود بن هلال المحاربي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tha'laba bin Zahdam al-Hanzali; Waki' bin al-Jarrah وكيع بن الجراح (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: “Allah, the Mighty and Sublime, said: I have never sent down My favor to My slaves but a group of them became disbelievers who say; “The stars and by stars.'”
Grade:

Hadith #1530 - Sunan al-Nasa'i - al-Aswad bin Hilal al-Maharbi الأسود بن هلال المحاربي; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tha'laba bin Zahdam al-Hanzali; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“It rained during the time of the Prophet (ﷺ) and he said: ‘Have you nt heard what your Lord said this night? He said: I have never sent down any blessing upon My slaves but some of them become disbelievers thereby, saying: ‘We have been given rain by such and such a star.’ As for the one who believes in Me and praises Me for giving rain, that is the one who believes in Me and disbelieves in the stars. But the one who says: ‘We have been given rain by such and such a star’ he has
Grade:

Hadith #1561 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; al-Aswad bin Hilal al-Maharbi الأسود بن هلال المحاربي; Ash'uth bin Qays; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tha'laba bin Zahdam al-Hanzali (Sunan al-Nasa'i)
“The people of the Jahiliyyah had two days each year when they would play. When the Messenger of Allah (ﷺ) came to Al-Madinah he said: ‘You had two days when you would play, but Allah (SWT) has given Muslims something instead that is better than them: the day of Al-Fitr and the day of Al-Adha.'”
Grade:

Hadith #4833 - Sunan al-Nasa'i - al-Aswad bin Hilal al-Maharbi الأسود بن هلال المحاربي; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Bashr bin al-Sari al-Afwah بشر بن السري أبو عمرو الأفوه; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tha'laba bin Zahdam al-Hanzali (Sunan al-Nasa'i)
there were two co-wives, one of whom struck the other with a tent people and killed her. The Messenger of Allah ruled that the Diyah was to be paid by the ‘Asabah of the killer, and that a slave should be given (as diyah) for the child in her womb. The Bedouin Said: “Are you penalizing me for one who neither ate nor drank, or shouted or cried (at the moment of birth)? Such a one should be overlooked/” He said: “Rhyming verse like the verse of the Jahiliyyah,” and he ruled that a slave
Grade:

Hadith #4834 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Aswad bin Hilal al-Maharbi الأسود بن هلال المحاربي; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tha'laba bin Zahdam al-Hanzali (Sunan al-Nasa'i)
“A woman of Banu Lihyan struck her co-wife with a tent pole and killed her, and the slain woman was pregnant. The Messenger of Allah ruled that the Diyah was to be paid by the’Asbah of the killer, and that a slave should be given (as Diyah) for the child in her womb”.
Grade: